2011
DOI: 10.1080/00380768.2011.637304
|View full text |Cite
|
Sign up to set email alerts
|

Fluxes of dissolved organic carbon and nitrogen throughout Andisol, Spodosol and Inceptisol profiles under forest in Japan

Abstract: Leaching of dissolved organic matter (DOM) is an important process in the translocation and stabilization of organic carbon (C) and in influencing nitrogen (N) availability in forest soils. The roles of DOM in soil carbon and nitrogen cycles were evaluated by quantifying the fluxes of dissolved organic carbon (DOC) and nitrogen (DON) entering and leaving the organic (O), A and B horizons. In Spodosol and Inceptisol soils, DOC fluxes were highest in the O horizon (149 to 344 kg C ha À1 yr À1 ), decreasing in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 52 publications
(46 reference statements)
3
3
0
Order By: Relevance
“…In general terms, the increase in DOC concentration from precipitation to throughfall is almost certainly due to leaf leaching and microbial metabolites (biodegradable and hydrophilic neutral carbohydrates) that wash from the canopy during this process (Guggenberger and Zech 1994;Michalzik et al 2001;Levia et al 2012). In this study site, the mean concentration of DOC in throughfall (6.84 ± 0.45 mg C L À1 ) consistent with previous reports (3-35 mg C L À1 , Michalzik et al 2001;Fujii et al 2011a), while the mean concentration of DOC in the precipitation (2.98 ± 0.45 mg C L À1 ) was a little higher than that reported in other studies (1.8-2.7 mg C L À1 ; Currie et al 1996;Michalzik and Matzner 1999;Moreno et al 2001;Solinger et al 2001). Contrary to expectations, the DOC concentration in throughfall below the dwarf bamboo (7.08 ± 0.42 mg C L À1 ) was not notably different from that in throughfall above the dwarf bamboo (6.84 ± 0.45 mg C L À1 ) ( Table 2), which indicates that the bamboo canopy had little effect on the DOC concentration.…”
Section: Variations and Regulation Of Doc Concentrationsupporting
confidence: 88%
See 2 more Smart Citations
“…In general terms, the increase in DOC concentration from precipitation to throughfall is almost certainly due to leaf leaching and microbial metabolites (biodegradable and hydrophilic neutral carbohydrates) that wash from the canopy during this process (Guggenberger and Zech 1994;Michalzik et al 2001;Levia et al 2012). In this study site, the mean concentration of DOC in throughfall (6.84 ± 0.45 mg C L À1 ) consistent with previous reports (3-35 mg C L À1 , Michalzik et al 2001;Fujii et al 2011a), while the mean concentration of DOC in the precipitation (2.98 ± 0.45 mg C L À1 ) was a little higher than that reported in other studies (1.8-2.7 mg C L À1 ; Currie et al 1996;Michalzik and Matzner 1999;Moreno et al 2001;Solinger et al 2001). Contrary to expectations, the DOC concentration in throughfall below the dwarf bamboo (7.08 ± 0.42 mg C L À1 ) was not notably different from that in throughfall above the dwarf bamboo (6.84 ± 0.45 mg C L À1 ) ( Table 2), which indicates that the bamboo canopy had little effect on the DOC concentration.…”
Section: Variations and Regulation Of Doc Concentrationsupporting
confidence: 88%
“…The growing season DOC flux was 311.5 kg ha À1 7 months À1 at the study site, which was in the upper range of those reported in other temperate forest ecosystems (100-400 kg C ha À1 year À1 , Michalzik et al 2001) and much higher than that reported in another deciduous forest in Steigerwald, Germany (85.9-208.2 kg C ha À1 year À1 ; Solinger et al 2001) and in Japan (52.6-343.6 kg C ha À1 year À1 ; Fujii et al 2011a). The magnitude of the DOC flux might be explained by several factors.…”
Section: Water Budgets and Dissolved Organic Carbon Flux During The Gmentioning
confidence: 51%
See 1 more Smart Citation
“…Besides cushion plants in the A horizon, mean DOC concentrations in our study (3.1 -4.0 mg L -1 ) are close to the range of values measured in Andosols grasslands: 4.7 mg L -1 (by wick samplers, Pesántez et al, 2018) and 5 -7 mg L -1 (by lysimeters, Ugolini et al, 1988). DOC concentrations present a larger range when measured in soil solutions collected by lysimeters for Andosols under other vegetation covers (2 -28 mg L -1 , Aran et al, 2001;Chen et al, 2017;Fujii et al, 2011).…”
Section: Soil Water Dynamics Under Cushion-forming Plants and Tussock...supporting
confidence: 86%
“…All three conditions are characteristics of a large portion of the Norwegian forest soils. In Japan, DOC flux rates from the O horizon were measured to 6-9 g C·m −2 ·year −1 , and of this flux, 0.9-2.8 g C·m −2 ·year −1 percolated into the B horizon (Fujii et al 2011). In the Fichtelgebirge, Bavaria, Germany, it was found that 2-5.5 kg C·m −2 (19%-50% of soil organic C) was sorbed, stabilized DOC in the soil profile (Kaiser and Kalbitz 2012;Kalbitz and Kaiser 2008).…”
Section: Factors Influencing Model Performance -Is Soil Type Important?mentioning
confidence: 99%